Evaluation of factors affecting external tibial torsion in patients with cerebral palsy - Min, Jae Jung; Kwon, Soon Sun; Kim, Kyu Tae; Choi, Young; Sung, Ki Hyuk; Lee, Kyoung Min; Park, Moon Seok (BMC Musculoskeletal Disorders, 2021)
Background: Gait deviation and associated torsional problems are common in patients with cerebral palsy (CP). Although femoral anteversion in CP has been extensively reviewed in previous studies, only a few studies have focused on tibial torsion. Therefore, this study aimed to evaluate tibial torsion in patients with CP and investigate the affecting factors. Methods: Consecutive patients with cerebral palsy who underwent 3-dimensional computed tomography for the assessment of rotational profiles were reviewed. Femoral anteversion and tibial torsion were measured, and the demographic characteristics of the patients were recorded. A linear mixed model was implemented to overcome the retrospective nature of the study. Results: After the implementation of inclusion and exclusion criteria, 472 patients were enrolled for this study. With age, external tibial torsion increased, while femoral anteversion decreased. The factors affecting external tibial torsion were increased femoral anteversion (p = 0.0057), increased age (p < 0.0001), higher Gross Motor Function Classification System (GMFCS) level (p < 0.0001), and involved/uninvolved limbs of hemiplegia (p = 0.0471/p = 0.0047). Conclusions: Older age, GMFCS level IV/V, hemiplegia, and increased femoral anteversion were the independent risk factors of increased external tibial torsion; therefore, performing an imaging study is recommended for assessing the extent of tibial torsion in patients with such characteristics.
Keywords: Aged; Cerebral Palsy; Femur; Gait; Humans; Retrospective Studies; Tibia; Torsion Abnormality; Cerebral palsy; Femoral anteversion; Gait deviation; Hemiplegia; Tibial torsion